Muhammad Al-Amîn Al-Syinqithy (W. 1393 H/ 1973 M) dan Karya Tafsîr Adhwâ’ Al- Bayân Fî Idhâh Al-Qur’ân Bî Al-Qur’ân - Ja'far Assagaf (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2013)
The study of Qur’anic interpretation has never been dry since the classical  era to the contemporary age right now. During its development, it had been able to bring and raised many figures and their monumental works. One of them who is brilliant is al-'Allama Muhammad al-Amin al-Syinqithy, with his book Adhwâ’ al-Bayân. This book of Qur’anic interpretation has been a critical spotlaght in the modern Muslim scholar. Through the book, alSyinqithy seek to understand the Qur'an by special character according to his personality and basic ability of the Qur’anic Interpretation. One of the discussion which is often be held among thinkers is the interpretation of one verse with another verse (Tasir al-Qur'an bi al-Quran). It is based on examples of the interpretation done by him in various verses of the Qur'an. The style of interpretation Fiqhi is also quite obvious in it. Simply i said, this book is very descent to be served as one of the intellectual wealth of Islam in the realm of Qur’anic interpretation study.